Hubungan Tingkat Pendidikan Ibu dengan Pengetahuan, Sikap, dan Praktik Pencegahan Demam Berdarah Dengue di Kota Banda Aceh - Funna, Desya Amalia; Asniar, Asniar; Alam, Teuku Samsul (Holistic Nursing and Health Science, 2024)
Dengue fever (DHF), one of the most concerning health problems in Indonesia.Individual knowledge, attitudes, and practices related to DHF are important factors that can influence the occurrence of DHF cases. Meanwhile, one of the determinants contributing to determining knowledge, attitudes, and practices is the level of educationand relationship these factors were not tested yet in Banda Aceh.Therefore, this studyfocusedon determining the relationship between mothers' education level and knowledge, attitudes, and practices of DHF prevention in Banda Aceh.This research was a descriptive correlative study with a cross-sectional approach involving 228 mothers living in villages with a high risk of DHF, selected using a proportional random sampling technique. Data were collected using a self-report questionnaire containing 62 statements to measure knowledge, attitudes, and practices of DHF prevention, then analyzed using the Kruskal Wallis test.The data analysis showed a relationship between the mother's education level and knowledge (p-value 0.00) about DHF and DHF prevention practices (p-value 0.033). Still, there was no relationship between the mother's education level and attitude (p-value 0.754) against DHF in Banda Aceh. This study indicates that maternal education factors need to be considered in planning community nursing interventions to increase knowledge and practice of dengue preventionthat is adjusted to the level of education of mothers in the community.